Private security companies and domestic violence: A welcome new development?. (September 2017) - Harkin, Diarmaid; Fitz-Gibbon, Kate
Due to the poor reputation of the private security industry and the multiple lines of concerns raised by scholars over the potentially corrosive costs of commercial security provision, it is important to consider whether for-profit companies are a welcome addition to the network of actors who respond to the needs of domestic violence victims. Using the case study of 'Protective Services' in Victoria, Australia, who appear to be one of the first known instances of a private security company offering services to victims of domestic violence, we argue that there may be advantages for victims engaging with commercial providers and reasons for optimism that commercial outfits can improve feelings of safety for a particularly vulnerable and under-protected population.